2019
DOI: 10.1111/jcmm.14883
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA LINC00673 silencing inhibits proliferation and drug resistance of prostate cancer cells via decreasing KLF4 promoter methylation

Abstract: | INTRODUC TI ONAs a non-skin tumour accompanied by variable natural history, prostate cancer is a highly prevalent malignancy and represents one of the leading causes of cancer-related deaths in the male populace. 1,2 Risk factors responsible for prostate cancer comprise smoking, alcohol consumption and levels of male androgens. 3 Paclitaxel is widely regarded as an essential important drug for prostate cancer treatment; however, paclitaxel resistance ensues in many prostate cancer patients, which highlights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…As a new tumor suppressor gene, KLF4 has a hypermethylated promoter sequence, and its gene expression is downregulated in prostate cancer, which promotes tumor proliferation and drug resistance. Downregulation of KLF4 or hypermethylation of KLF4 gene promoters can be considered markers for predicting the early recurrence of cancer [22,23]. GSTP1 is functionally inactivated by promoter methylation, which increases the sensitivity to oxidative stress and increases the risk of prostate cancer progression [24].…”
Section: Discussionmentioning
confidence: 99%
“…As a new tumor suppressor gene, KLF4 has a hypermethylated promoter sequence, and its gene expression is downregulated in prostate cancer, which promotes tumor proliferation and drug resistance. Downregulation of KLF4 or hypermethylation of KLF4 gene promoters can be considered markers for predicting the early recurrence of cancer [22,23]. GSTP1 is functionally inactivated by promoter methylation, which increases the sensitivity to oxidative stress and increases the risk of prostate cancer progression [24].…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, KLF4 function is frequently lost due to hypermethylation of CpG islands in the promotor region [159]. Suppression of LINC00673 led to improved chemosensitivity through increased KLF4 activity in both in vitro and in vivo experimental models and additionally reduced proliferation in PCa cell lines [38]. This is in line with results in gastric cancer, where epigenetic suppression of KLF4 through LINC00673 was associated with poor OS (HR = 2.989, 95%CI 1.126-5.178, p = 0.001) [160].…”
Section: Linc00673mentioning
confidence: 99%
“…Some reports indicate that KLF4 promotes prostate cancer growth [ 94 , 95 ] while other reports claim the opposite [ 96 , 97 , 98 ]. Some research teams discovered that KLF4 is upregulated in prostate tumor samples [ 95 ] while other reports claim that the levels of KLF4 are in fact reduced in prostate cancer [ 96 , 97 , 98 ]. In one study, KLF4 was detected primarily in the cytoplasm of non-tumor prostate tissues, and it was suggested that subcellular localization of KLF4 may be an important factor in prostate cancer [ 98 ].…”
Section: Prostate Cancermentioning
confidence: 99%
“…In prostate cancer this feedback loop is dysregulated due to the disrupted miR-7 processing, which leads to the overexpression of KLF4, maintaining stemness of prostate cancer stem cells to promote tumor growth [ 94 ]. The expression of KLF4 is negatively regulated by lncRNA LINC00673 [ 96 ]. LINC00673 binds to the KLF4 promoter and recruits DNMT1, DNMT3a and DNMT3b.…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation